Anxiety and Depression Among Dentists in the Kingdom of Saudi Arabia - Mohamed Asif S; Ibrahim Assiri K; Mohammed Al Muburak H; Hamid Baig FA; Abdullah Arem S; Arora S; Mohammed Shamsudeen S; Shariff M; Shamsuddin S; Mohammed Lahiq AA (Dove Medical Press, 2022)
Shaik Mohamed Asif,1 Khalil Ibrahim Assiri,1 Hussain Mohammed Al Muburak,1 Fawaz Abdul Hamid Baig,2 Saeed Abdullah Arem,1 Suraj Arora,3 Shaik Mohammed Shamsudeen,1 Mansoor Shariff,4 Shaheen Shamsuddin,5 Anas Abdullah Mohammed Lahiq4 1Department of Diagnostic Science and Oral Biology, College of Dentistry, King Khalid University, Abha, Kingdom of Saudi Arabia; 2Department of Oral and Maxillofacial Surgery, College of Dentistry, King Khalid University, Abha, Kingdom of Saudi Arabia; 3Department of Restorative Dental Sciences, College of Dentistry, King Khalid University, Abha, Kingdom of Saudi Arabia; 4Department of Prosthetic Dentistry, College of Dentistry, King Khalid University, Abha, Kingdom of Saudi Arabia; 5Department of Orthodontics, College of Dentistry, King Khalid University, Abha, Kingdom of Saudi ArabiaCorrespondence: Shaik Mohamed Asif, Department of Diagnostic Science and Oral Biology, College of Dentistry, King Khalid University, Abha, 61421, Kingdom of Saudi Arabia, Tel +966 557361821, Email masif020@gmail.comPurpose: Dentists face a great deal of professional stress, in dental school and in practice. Their personal, as well as professional lives, get affected negatively by stress and poor mental health. This study aims to evaluate anxiety and depression among dentists of Abha in kingdom of Saudi Arabia.Materials and Methods: A cross-sectional study was carried out among 246 registered dentists of Abha to assess anxiety and depression. Participants willing to participate, and completely filled questionnaire were included in study. Data regarding demography, work-related characters, lifestyle and self-reported physical and mental status were collected. Mental status was measured by using pre validated questionnaire Zung Self-Rating Anxiety Scale (SAS) and the Zung Self-Rating Depression Scale (SDS). Data were analyzed using Statistical Package for Social Sciences (SPSS 20) by IBM. Descriptive statistics, Pearson correlation, independent t test and one way ANOVA were used to analyze the data at the significant interval of p≤ 0.05.Results: Different levels of anxiety and depression were noticed both in males and female dentist. There was no statistical difference in the mean scores between males and females. There was a statistical difference of anxiety and depression scores noticed among dentist working in government institution, with five to ten years of experience. Habits of smoking were shown to significantly affect the risk of anxiety and depression scores.Conclusion: Dentist due to nature of the practice are prone for anxiety and clinical depression. Stress coping methods should be included in dental curriculum which would indirectly improve professional abilities and personal life.Keywords: anxiety, dentists, depression